Novel Krisis Karya Alias Ali : Satu Analisa - Mahmud, Bashah (Universiti Sains Malaysia, 1977)
Alias All besides writing short stories also writes novels.In this dissertation I have chosen hie second novel KRISIS called "KRISIS by Alias Ali : An analysis".Alias Ali used the incidents during the elections of 1955 and 1959 in his honetown of Kuala Brang, Terengganu as a background for his KRISIS.The novel though in the form of a 'reportage' was turned into a novel by Alias through his abilities in creative writing.By using reality as its foundation Alias in such a way turned it into a fictious work.